Performance of Sports Goods Industry in Punjab - A Comparative Analysis - Sidhu, H. S.; Kumar, Gulshan (Indian Journal of Marketing, 2006)
Punjab occupies a position of pride in the industrial map of India. Before independence, there were a few manufacturing centers in Punjab which were famous for industries, viz., Batala for foundries, Amritsar for woolen textile, Kartarpur for furniture and Ludhiana for hosiery but due to partition of the country, new industries like handtool, surgical instruments and sports goods appeared in Punjab (Lal, 1966). Now, Punjab leads in manufacture of machine and handtools, bicycle and bicycle parts, sewing machines, woolen&hosiery items and sports goods. As far as sports goods industry is concerned, it has witnessed a phenomenal growth over the past five decades and now occupies a place of prominence in Punjab’s economy in view of its massive potential for employment and growth. The sports goods industry of Punjab is a highly labour intensive industry providing employment to a large number of women as well as weaker sections of the society. "The only industry which appears to offer some prospects to Punjab is sports goods" (Chandra Mohan, 2002).